(untitled) (Al-Farooq Journal of Sciences, 2026)
The study aimed to identify the impact of information systems use on improving administrative performance at the College of Science and Technology – Adiri, by examining the dimensions of information systems use, namely technical infrastructure, information quality, employee competence, and training and technical support, and determining their impact on administrative performance in terms of the speed of task completion, performance accuracy, quality of administrative work, reduction of errors, and effective utilization of time and effort. The study adopted the descriptive-analytical approach and used a questionnaire as a tool for collecting data and analyzing the opinions of the study sample. The results showed that the level of information systems use was moderate, while the level of administrative performance was good. The findings also revealed a statistically significant impact of information systems use on improving administrative performance, with information systems use explaining 61.2% of the variance in administrative performance, while the remaining 38.8% was attributed to other factors. The results further indicated a statistically significant impact of the dimensions of information systems use on improving administrative performance. Information quality ranked first in terms of the strength of its impact, followed by employee competence, technical infrastructure, and training and technical support, respectively. Based on the results of the hypothesis testing, the main hypothesis and all sub-hypotheses, which stated that there is a statistically significant impact of information systems use and its dimensions on improving administrative performance at the College of Science and Technology – Adiri, were accepted. The study recommended the development of the technical infrastructure, improvement of information quality, enhancement of employee competence, and strengthening of training and technical support programs, in a manner that contributes to developing administrative performance and improving the quality of work within the college.